Global proteomic analysis of lysine acetylation in zebrafish (Danio rerio) embryos. Issue 23 (2nd November 2016) - Kwon, Oh Kwang; Kim, Sunjoo; Lee, Sangkyu
Abstract : Lysine acetylation is an important post‐translational modification (PTM). Since the development of MS‐based proteomics technology, important roles of lysine acetylation beyond histones have focused on chromatin remodeling during the cell cycle and regulation of nuclear transport, metabolism, and translation. Zebrafish ( Danio rerio ) is a widely used vertebrate model in genetics and biologic studies. Although studies in several mammalian species have been performed, the mechanism of lysine acetylation in D. rerio embryos is incompletely understood. Here, we investigated the global acetylome in D. rerio embryos by using an MS‐based proteomics approach. We identified 351 acetylated peptides and 377 nonredundant acetylation sites on 189 lysine‐acetylated proteins in 5‐day postfertilization (hpf) embryos of D. rerio . Among lysine‐acetylated peptides, 40.2% indicated three motifs: (ac)KxxxK, (ac)KxxxxK, and Lx(ac)K. Of 190 acetylated proteins, 81 (42.6%) were mainly distributed in the cytoplasm. Gene ontology enrichment and Kyoto Encyclopedia of Genes and Genomes pathway analyses showed that lysine acetylation in D. rerio was enriched in metabolic pathways. Additionally, 17 of 30 acetylated ribosomal proteins were evolutionarily conserved between zebrafish and humans. Our results indicate that acetyllysine might have regulatory effects on ribosomal proteins involved in protein biosynthesis.